Politik Uang dan Prospek Konsolidasi Demokrasi Indonesia - Ali Nurdin (Mahesa Research Center, 2021)
Until the fifth legislative election (2019) in the Reformation Era, money politics was still a disease in the democratic process in Indonesia. Instead of decreasing, the practice of money politics in the last election has become even more massive, vulgar, and brutal. Meanwhile, the prospect of Indonesian democracy, which was considered optimistic, so that it is considered a new democracy has recently tended to decline. This study tries to see the link between money politics and the prospect of consolidating Indonesia's democracy by utilizing secondary data through a qualitative descriptive study. The results of the study show that the quality of Indonesian democracy has decreased in recent years, partly due to the proliferation of political corruption practices, including money politics. Indonesia's prospects for a developed and stable democracy still require a long struggle, especially regarding serious eradication of political corruption, including corruption related to elections such as money politics.